EVM Analysis for Broadband OFDM Direct-Conversion Transmitters - Gregorio, Fernando Hugo (2013)
Low-cost OFDM direct-conversion transceivers suffer from signal degradation through the impairments of the analog front-end, e.g., due to in-phase and quadrature (IQ) imbalance, phase noise, and nonlinear power amplifier (PA) effects. This work analyzes the joint performance degradation due to these key transmitter imperfections. Error vector magnitude (EVM) is chosen as the figure of merit, which is motivated by its frequent use in the standards for specifying transmitter requirements. In particular, we derive closed-form EVM expressions for the challenging problem of wideband OFDM transmitter design, and validate the analysis through simulations. Based on the study it is possible to conclude that EVM is governed by the memory effects associated to the PA and the reciprocal of image rejection ratio (IRR), defined by the IQ modulator. We also demonstrated that the intercarrier interference (ICI) due to the local oscillator phase noise shows an approximately frequency-flat response.